Y-8=-11

Simple and best practice solution for Y-8=-11 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for Y-8=-11 equation:


Simplifying
Y + -8 = -11

Reorder the terms:
-8 + Y = -11

Solving
-8 + Y = -11

Solving for variable 'Y'.

Move all terms containing Y to the left, all other terms to the right.

Add '8' to each side of the equation.
-8 + 8 + Y = -11 + 8

Combine like terms: -8 + 8 = 0
0 + Y = -11 + 8
Y = -11 + 8

Combine like terms: -11 + 8 = -3
Y = -3

Simplifying
Y = -3

See similar equations:

| -3-2(4x-13)=-40+7 | | -5(1+5x)=-180 | | 2x-16=3x-19 | | 3x+4=5x-5+2x-1 | | 2(x+8)-10= | | 4h=19 | | x(2-x)-3x(x+5)= | | (-5/3w)-(4/3)=w-(5/4) | | -4+0=-4 | | Y+-9=y-9 | | 4(6)+2=26 | | 1.2+0.2=0.8 | | 15=5x+x+9 | | 20-2*7+1-(-3)+10=x | | 12z+-19z=14 | | 3x-1+3x+1=3x | | 3xy=-2y | | 2w(w+9)= | | 2k=3 | | 6y=16-2y | | 3(-3x-6)=63 | | 2x-16=5+x-6 | | -7y-8y=-23 | | -72-3y=-12x | | -6(2d-2)=24 | | -2x+9=9-2x | | 2/6=5/z | | -5/2x=15/4 | | 10m-10m+m=11 | | 6(-3x+9)=234 | | -315=5(-8k+1) | | 5+-2x=-3 |

Equations solver categories